Radiation exposure and the justification of Computed Tomography scanning in King Abdul-Aziz Specialist Hospital Emergency Department Taif City, KSA - AL-Otaibi, Osama Awad Najem; AL-Thobaiti, Yazeed S; Malibari, Hassan Abdulfattah; AL-Malki, Mansour Jaman; AL- Thobaiti, Ahmed Abdulrahman Mohammed; AL-Beshri, Bashair Saud; AL-Harthi, Khalid Sultan; AL-Harthi, Rayan Mohammed; AL-Manjoumi, Meshari Abdulrahman; AL-Faqih, Rakan Helal (Journal of Posthumanism, 2024)
Background: The dire consequences of unjustified exposure to radiation, mainly MDCT, for emergency patients are considered public health issues, so this study is conducted to determine the necessity of radiologist discussion and minimize unjustified exposure to MDCT. Material and Method: A total of 770 patients were retrospectively exposed to MDCT, and the effective dose (mSv)for each patient was calculated using DLP Multiplied by a tissue weighting factor, extending from (1 September to 31 December 2024). 128 slice CT systems (Siemens Medical System) King Abdul-Aziz Specialist Hospital (KAASH) in Ta’if City, the Kingdom of Saudi Arabia. Result: In this retrospective study, a total of 770 patients were referred to the radiology department from the emergency department for a MDCT 570 (74%) were male, and 200 (26%) were female. The results have observed that exposure to ionizing radiation was significantly higher in the male population (74%) than in the female population (26%). Based on age groups, the rate of exposure to ionizing radiation was 33.8%, 20.8%, 10.4%, 13%, 8.4%, and 13.6% for the age range 15-25 years, 26-35 years, 36-45 years, 46-55years 56 -65 years, and 66y and older respectively. According to statistical analysis, most cases requested directly by an ER resident with a specialist or consultant agreement to exposed to ionizing radiation (MDCT) were normal which, representing 470 (61%). In comparison, they were abnormal, representing 250 (32.5%), and the other findings were related to the patient’s age, which represented 50 (6.5%). The brain was found to be the most frequent part exposed to ionizing radiation with an incidence of 295 (38.3%), followed by KUB with an incidence of 155 (20.1%), whole spine 78 (10.1 %), chest as well as the abdomen and pelvis represent 65(8.4%), facial bone 60 (7.8%) while the upper/lower extremities were the least region that exposed to MDCT which represents 52 (6.8%). The average effective radiation dose of each patient was still within the optimal range of the recommended dose as a result of the efficacy, effectiveness, and qualification of a technologist as well as the radiologist and medical physicist. Conclusion: The ALARA concept and radiologist discussion are essential to avoid unnecessary CT imaging, diminish or minimize unjustified CT requests, also Education for dose reduction programs is highly recommended.